1999
DOI: 10.1097/00005537-199903000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Nasal alar reconstruction: A critical analysis using melolabial island and paramedian forehead flaps

Abstract: More favorable aesthetic and functional outcomes are seen with single subunit cutaneous alar defects reconstructed with the melolabial island flap than with deep composite or extensive unilateral nasal defects reconstructed with the paramedian forehead flap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 8 publications
4
36
1
Order By: Relevance
“…10,[12][13][14][15][16] Seven patients (18 percent) had postoperative complications requiring revision. Compared with earlier reported postoperative complication rates (1 to 20 percent), 10,12-16 this seems slightly high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,[12][13][14][15][16] Seven patients (18 percent) had postoperative complications requiring revision. Compared with earlier reported postoperative complication rates (1 to 20 percent), 10,12-16 this seems slightly high.…”
Section: Discussionmentioning
confidence: 99%
“…10 -16 Only four outcome studies of nasal reconstruction actually presented any data on subjective aesthetic results: one without any statistical analyses, 11 one without finding any statistically significant results because of small sample sizes, 12 one with subjective nasal functional ratings by 32 patients and subjective aesthetic ratings by a panel, 14 and one for nasal alar defects only. 15 A PubMed search found no studies addressing objective functional outcome after subtotal nasal reconstruction.…”
mentioning
confidence: 99%
“…1 Another study performed on singlestage nasolabial transposition flaps revealed no complete failures and 6.7% partial failures. 4 Considering the results from these 2 studies in conjunction with zero partial failures in our series, one may assume that partial failures may be more likely in NLFs when they were used ARCH OTOLARYNGOL HEAD NECK SURG/ VOL 138 (NO.…”
Section: Commentmentioning
confidence: 94%
“…In order to achieve functional and aesthetic results, all layers influenced by the surgical defect must be tended to and replaced. Traditional surgical teaching has held that if a defect involves the lining of the nostril in addition to the cutaneous covering of the nose, it should be repaired in one of two ways: either via a folded paramedian forehead flap (PMFF) [8][9][10][11] or an intranasal lining flap with free cartilage graft and additional cutaneous flap [12,13] . Repairing the internal lining of the nose or the -mucosa‖ is imperative in that the mucosa filters, warms, and doi: 10.18282/jsd.v1.i3.47 humidifies incoming air.…”
Section: Introductionmentioning
confidence: 99%
“…Intranasal lining flaps can resurface the nostril lining defects and provide blood supply for the overlying cartilage graft [12][13][14][15][16] . However, each of these procedures comes with its respective disadvantages.…”
Section: Introductionmentioning
confidence: 99%